2011
DOI: 10.1136/thoraxjnl-2011-200489
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in movies and adolescent smoking: cross-cultural study in six European countries

Abstract: Aim To investigate whether the association between exposure to smoking in movies and smoking among youth is independent of cultural context. Method Cross-sectional survey of 16 551 pupils recruited in Germany, Iceland, Italy, the Netherlands, Poland and Scotland with a mean age of 13.4 years (SD=1.18) and an equal gender distribution. School-based surveys were conducted between November 2009 and June 2010. Using previously validated methods, exposure to movie smoking was estimated from the 250 top-grossing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 36 publications
4
67
2
6
Order By: Relevance
“…However, patients can also empower themselves through selfeducation facilitated by for example internet or television [15]. In fact, previous studies showed that television is a powerful medium in influencing people's behavior [16][17][18] and that the majority of elderly patients obtain information about cardiopulmonary resuscitation (CPR) from television [19]. However, a previous study showed that in movies dealing with life-threatening illness and death the level of reality is limited [20].…”
Section: Introductionmentioning
confidence: 96%
“…However, patients can also empower themselves through selfeducation facilitated by for example internet or television [15]. In fact, previous studies showed that television is a powerful medium in influencing people's behavior [16][17][18] and that the majority of elderly patients obtain information about cardiopulmonary resuscitation (CPR) from television [19]. However, a previous study showed that in movies dealing with life-threatening illness and death the level of reality is limited [20].…”
Section: Introductionmentioning
confidence: 96%
“…12,19,20 In this study, 16 551 adolescents from 6 countries (from Germany, Iceland, Italy, Poland, Netherlands, and Scotland) were interviewed at baseline, and .80% of these were followed up 12 months later. The sample size of this study provides a unique opportunity to perform subsample analyses such as the one outlined earlier.…”
mentioning
confidence: 99%
“…[30] To our knowledge the effect of printed media imagery on smoking uptake has not been explored, but we see no reason to believe that positive imagery of the kind we have documented is any less likely to have an effect on behaviour in young people than that in film. Social learning theory suggests that behaviour is often learned through imitating models, [31] and thus readers exposed to images of their favourite celebrities smoking may initiate smoking intentions in the same way as research reported on smoking in films, [29] because they aspire to be like them. Such instances may also normalise the act of smoking amongst current smokers and those thinking about starting smoking, for example by triggering the urge to smoke among non-smokers.…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…Whilst this requires further investigation, we would argue that stricter regulation is required along with working with television and film content regulators, particularly to reduce high levels of adolescent exposure to such images, which has been found to impact smoking initiation. [11,29] Only a small number of tobacco-related references appeared to discourage smoking, and these cases were predominant in sections where readers were seeking advice from health experts about smoking cessation. These instances need to be considered in relation to the entire content of the magazines, where anti-smoking references were presented in the same issue showing many more instances that were pro-smoking.…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
See 1 more Smart Citation